Segmentation of the buffalo meat consumer market in Belém, Pará, Brazil - MARQUES, Cristiane Soares Simon (Universidade Federal do Pará, 2018)
The objective of this study was to identify different market segments for buffalo meat with target groups defined in the city of Belém, Pará, Brazil. Paired samples of beef and buffalo meat were given to 447 volunteers, and a sensory analysis of the products was conducted. After the tasting, a questionnaire was administered to obtain demographic (age, educational level, marital status) and economic (household income) data as well as information on the habits of respondents and preferences regarding buffalo meat. The factors were estimated using the principal components method and the factors with characteristic roots greater than one were extracted. To check the suitability of the factorial model, Bartlett’s sphericity test and the Kaiser-Meyer-Olkin (KMO) test were used. A factor analysis was performed, identifying five factors with common variability dimensions. The study has helped identify four distinct market segments which, combined with a targeted marketing strategy, can be used to leverage the productive chain: I - Young and interested, II - Mixed and indifferent, III - Graduates and successful, and IV - Healthy women. All had positive responses to buffalo meat; clusters I and III stood out with regard to several indicators, especially those related to the preference for buffalo meat and the predisposition to purchase and include it in meals. The sensory analysis indicated that consumers showed a greater acceptance of buffalo meat based on the characteristics of flavour, colour, succulence and tenderness. The study helps to identify market segments with distinct features that, combined with a targeted marketing strategy, can be used to leverage the supply chain.